Evaluation of the Physical and Chemical Profiles of Instant Rice Based on Germinated Brown Rice of Inpari 32 Variety - Desy Triastuti; Fitri Audia; Enceng Sobari; Rafi Fauzan (Jurnal Teknik Pertanian Lampung (Journal of Agricultural Engineering), 2026)
Brown rice is dehulled rice that retains its bran layer and therefore has higher fiber and nutrient content than white rice. Germination and instant processing are applied to improve the quality of brown rice and shorten cooking time. This study aimed to evaluate the effects of soaking duration (12 and 24 h) and germination time (36, 48, and 60 h) on the physical and chemical properties of instant rice produced from germinated brown rice (GBR) of the Inpari-32 variety, using a nested randomized block design. Variables for GBR included yield, radicle emergence, moisture content, ash content, and amylose content, while instant rice was evaluated for bulk density, yield, moisture content, ash content, and amylose content. Data was analyzed using ANOVA followed by DMRT at the 5% significance level. Results showed that soaking and germination duration had no significant effect on GBR yield or amylose content of instant rice, whereas germination time significantly affected GBR moisture and ash content, which ranged within national quality limits. The resulting instant rice had low bulk density, acceptable moisture content, and relatively high ash (mineral) content. A combination of 12 h soaking and 36 h germination is recommended as an efficient treatment to produce instant rice from GBR with acceptable physical and chemical quality.